2020
DOI: 10.1177/1356766720975047
|View full text |Cite
|
Sign up to set email alerts
|

Sharing travel related experiences on social media – Integrating social capital and face orientation

Abstract: Tourists can share their travel experiences or related information freely through social media platforms. The purpose of this research is to explore the factors associated with sharing travel related experiences on social media by travellers in the context of social capital theory and person-context interaction theory. Data were collected among consumers in Malaysia using a structured survey; 423 responses were generated. The findings show that the social capital dimensions (social ties, trust, reciprocity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 80 publications
2
7
0
1
Order By: Relevance
“…Cognitive capital refers to a common context that increases understanding among people represented by shared language, vision, and goals (Nahapiet & Ghoshal, 1998). Cognitive capital highlights the shared vision predicated on a common language, shared meanings, and an understanding of values and goals among the people within the network (Kumar et al, 2020). Relational capital pertains personal relationships between people that arise from interpersonal contacts such as respect, support, and trust (Nahapiet & Ghoshal, 1998).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Cognitive capital refers to a common context that increases understanding among people represented by shared language, vision, and goals (Nahapiet & Ghoshal, 1998). Cognitive capital highlights the shared vision predicated on a common language, shared meanings, and an understanding of values and goals among the people within the network (Kumar et al, 2020). Relational capital pertains personal relationships between people that arise from interpersonal contacts such as respect, support, and trust (Nahapiet & Ghoshal, 1998).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Un buen ejemplo de esto es el comportamiento del consumidor de viajes, y el modo en que éste planifica su ruta turística y la comparte con sus familiares y allegados (Kaplan y Haenlein, 2010). Los investigadores Kumar, Goh y Balaji, tal y como señalaba Toffler, inciden en la capacidad de los medios sociales de propiciar que los viajeros consuman, produzcan y distribuyan contenidos relacionados con sus experiencias viajeras, produciéndose además una colaboración con proveedores de servicios turísticos (Kumar et al, 2021).…”
Section: Redes Sociales Y Turismounclassified
“…Munar et al (2014) found that altruistic motivation and community-related motivation were most related to information sharing, and motivational factors varied according to content types and social media types [7] . Lehto et al (2018) found that the emotional intensity of disabled tourists had an impact on their tourism sharing [8] . Kumar et.al (2021) pointed that the social capital dimensions (social ties, trust, reciprocity and shared vision) positively impact sharing intention on social media while identification doesn't impact the sharing intention [9] .…”
Section: Factors Influencing Sharing Behaviours Of Wechat Usersmentioning
confidence: 99%